Towards a Virtuosity of School Leadership: clinical support and supervision as professional learning. Issue 4 (8th August 2022) - Bainbridge, Alan; Reid, Hazel; Del Negro, Gaia
ABSTRACT: This paper introduces an innovative clinical support and supervision project that has its origins in the concern for how senior school leaders are increasingly being expected to manage the escalating demand to care for pupils, families and often the wider community. In response to these pressures we offer a three-stage professional learning model of supervision which encompasses collaboration, reflection and dialogue, while facilitating the development of professional skills within a non-judgemental space for personal and professional reflexivity. Alongside providing the service, the authors undertook two phases of qualitative research over a five-year period. Our findings indicate that support and supervision has been wholly beneficial identifying a positive impact across three broad themes: Professional learning, health and well-being, and wider school culture. The process facilitates headteachers making professionally situated decisions grounded in an understanding of educational purpose. We call for a virtuosity of school leadership – a practice of educational leadership where decision-making is informed by good educational judgements and not by standardisation and punitive accountability measures. Distinctively, clinical support and supervision promotes a virtuosity of school leadership while also meeting the moral obligation to care for school leaders and in doing so those in their care.